Sub-5 nm homeotropically aligned columnar structures of hybrids constructed by porphyrin and oligo(dimethylsiloxane). Issue 1 (7th December 2021) - Yang, Weilu; Liu, Dong; Luo, Longfei; Li, Peiyun; Liu, Yun; Shen, Zhihao; Lei, Ting; Yang, Huai; Fan, Xing-He; Zhou, Qi-Feng
Abstract : Disc–coil hybrid liquid crystals containing porphyrin and oligo(dimethylsiloxane) can form lamellar and columnar phases that can also be transferred onto a silicone substrate with adjustable orientation. Abstract : A series of tetraphenylporphyrin-based thermotropic liquid crystals containing oligo(dimethylsiloxane) were synthesized. These disc–coil hybrids form ordered nanostructures with periodic sizes on the sub-5 nm scale, including oblique columnar, lamellar, and hexagonal columnar phases. Films with sub-5 nm line patterns and homeotropically aligned columnar structures can be obtained by substrate-induced self-assembly.